The social worker’s work process in the socio-legal space to strengthen social rights in the exercise of citizenship (Research, Society and Development, 2023)
This article aims to explain the work process of Social Workers in the implementation of social rights and the exercise of citizenship in the socio-legal space. This area of activity is the area where the correlation of forces is defined by compliance with laws, which, therefore, also reflects the clash of the class struggle, and the Social Worker's action scenario is to do so using the investigation with a qualitative approach with bibliographic and documentary research.